Reproductive timing and clutch parameters of the pearl darter, Percina aurora , in the Pascagoula River drainage - Malia B. Davidson; Noah J. Daun; Scott R. Clark; Brian R. Kreiser; Jake F. Schaefer (Journal of Fish Biology, 2026)
Understanding the timing, duration and effort put into reproduction is vital to successful management of any species. The southeastern United States is home to tremendous levels of aquatic biodiversity and was recently named one of the Earth's biodiversity hotspots. For some species, the fundamentals of age, growth, reproductive timing and ecology remain poorly understood. Percina aurora , the pearl darter, has been recently listed as threatened due to its contracting range, likely due to anthropogenic pressure on these systems. However, management efforts are hindered by the lack of knowledge about the life history of P. aurora . The purpose of this project was to examine the age, growth and reproductive ecology of P. aurora in the Pascagoula River basin of southeastern Mississippi, USA. To do this, we compiled length data from recent field collections and catalogued museum specimens to estimate age and growth, as well as clutch parameters (GSI, egg size) to infer reproductive output. We also used larval fish metabarcoding to confirm successful spawning of P. aurora . These results indicate P. aurora exhibits a protracted, potentially batch‐spawning reproductive strategy with consistent spawning timing across rivers, supported by both growth models and larval detections.

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

The interplay of geography and urbanization shapes morphological variation in the common toad, Rhinella arenarum - Laura C. Pereyra; Mario R. Ruiz-Monachesi; Rebeca Acosta; Dionel Aguiar; Clarisa L. Bionda; Ana G. Boggio; Rocío P. Demartín; Romina Ghirardi; Pablo R. Grenat; Javier A. López; Guillermo Natale; Lorena B. Quiroga; et al. (Urban Ecosystems, 2026)

Retroperitoneal T-cell lymphoma with cystitis and megacolon in a young feline leukaemia virus-positive cat - Gabriela Hartmann; Simone S.M. Cruz; Joanna V.Z. Echenique; Rafael B. Rosa; Gabriela C. Schaefer; Álan G. Pöppl; Saulo P. Pavarini (Journal of Comparative Pathology, 2026)

Variability in the thermospheric neutral mass density: A multiple model comparison - Yongliang Zhang; Patrick B. Dandenault; Larry J. Paxton; Robert Schaefer; Clayton Cantrall; Hyosub Kil; Rafael Mesquita; Matthew E. Zuber (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Effective treatment of energetic containing wastewater in a sequential anaerobic-aerobic membrane bioreactor (MBR) system - Part 1: Treatment of IMX-104 wastewater - Mark E. Fuller; Paul C. Hedman; Kung-Hui Chu; Todd S. Webster; Charles E. Schaefer; Danielle N. Tran; Paul B. Hatzinger (Chemosphere, 2025)

P19-03 The pyrrolizidine alkaloid lasiocarpine impairs cell cycle progression in vitro - S. Hessel-Pras; M. Beckschulte; A. Peters; A. Stahl; M. Templin; H. Sprenger; L. Boehmert; J.-H. Kuepper; B. Sachse; B. Schaefer (Toxicology Letters, 2025)

Long term assessment of SARS-CoV-2 in wastewater and the transition to evaluate additional viral targets - Ayaaz Amirali; Mark E. Sharkey; Shruti Choudhary; Kristina M. Babler; Cynthia C. Beaver; Pratim Biswas; Kate R. Bowie; Taylor Burke; Benjamin B. Currall; George S. Grills; Hannah G. Healy; Alexander G. Lucaci; et al. (Science of The Total Environment, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Evaluating the role of binge planning and binge inevitability within affect regulation models of binge eating - Glen Forester; Lauren M. Schaefer; Jeffrey S. Johnson; Brianne N. Richson; Robert D. Dvorak; Ross D. Crosby; Carol B. Peterson; Stephen A. Wonderlich (Appetite, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Influence of habitat features on the colonisation of native and non-indigenous species - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Cian Foster-Thorpe; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Shinichi Nakagawa; Craig D.H. Sherman; Maria L. Vozzo; Katherine A. Dafforn (Marine Environmental Research, 2024)

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Original plant diversity and ecosystems of a small, remote oceanic island (Corvo, Azores): Implications for biodiversity conservation - Simon E. Connor; Tara Lewis; Jacqueline F.N. van Leeuwen; W.O. (Pim) van der Knaap; Hanno Schaefer; Nicholas Porch; Ana I. Gomes; Stephen B. Piva; Patricia Gadd; Petr Kuneš; Simon G. Haberle; Matthew A. Adeleye; et al. (Biological Conservation, 2024)

Variable effects of substrate colour and microtexture on sessile marine taxa in Australian estuaries - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Craig D. H. Sherman; Cian Foster-Thorpe; Maria L. Vozzo; Katherine A. Dafforn (Biofouling, 2024)

P26-05: Pyrrolizidine alkaloids stimulate different molecular pathways in target organs and verification of in vivo response using human in vitro models - J. Buchmueller; J. Ebmeyer; H. Sprenger; M.P. Beckschulte; O. Creutzenberg; D. Schaudien; A. Braeuning; B. Schaefer; S. Hessel-Pras (Toxicology Letters, 2023)

Beyond habitat boundaries: Organic matter cycling requires a system‐wide approach for accurate blue carbon accounting - Johannes Renke Krause; Alejandro Hinojosa‐Corona; Andrew B. Gray; Juan Carlos Herguera; Julianna McDonnell; Michael V. Schaefer; Samantha C. Ying; Elizabeth Burke Watson (Limnology and Oceanography, 2022)
As coastal ecosystems become widely recognized for their capacity to sequester carbon (blue carbon), standard accounting methodologies for the generation of carbon credits are being developed. To ensure the applicability of these standards across blue carbon ecosystems, we investigated organic carbon provenance and burial in salt marshes and seagrass meadows of an arid, upwelling‐dominated Eastern Pacific lagoon. We found low carbon density in benthic sediments of Bahía de San Quintín (5.9 ± 0.5 mg C cm −3 ), only marginally higher in Zostera marina beds (6.9 ± 0.5 mg C cm −3 ), likely due to remineralization and hydrodynamically driven export of seagrass material, resulting in low carbon burial rates (4.5 ± 2.5 g C m −2 yr −1 ). Sediment organic carbon is mainly controlled by the fraction of fine sediment and its source is largely allochthonous, although sources differ spatially. Salt marshes at San Quintín derive 40% of their organic matter from autochthonous material and exhibit higher carbon burial rates (up to 414.7 ± 28.6 g C m −2 yr −1 ) and sediment carbon densities (32.0 ± 0.7 mg C cm −3 ) compared to benthic sediments. This study emphasizes the connectivity of blue carbon habitats with marsh plant detritus supplementing benthic carbon burial and incorporation of detrital eelgrass in marsh sediments. Our findings highlight the importance of allochthonous organic matter for carbon sequestration in blue carbon habitats, suggesting standard accounting practices that deduct allochthonous organic matter would miss the full potential for carbon burial.

Light-level geolocation reveals the short-distance non-breeding movements and distribution of tufted puffins throughout the Northeast Pacific Ocean - Anne L. Schaefer; Kristen B. Gorman; Mary Anne Bishop (Frontiers in Marine Science, 2022)
Comprehensive assessments of cumulative impacts to seabirds have been hindered by an incomplete understanding of temporal and spatial patterns in marine habitat use, particularly during the non-breeding season when seabirds can range widely across the global ocean. Alcids are an important component of the meso-predator biodiversity of the North Pacific Ocean, yet the non-breeding movement ecology and distribution for many of the Pacific Auk species remain poorly quantified. Recent and projected declines for historically robust populations of tufted puffin ( Fratercula cirrhata ) in Alaska highlight the importance of resolving aspects of the species’ non-breeding ecology, especially the pelagic phenology and distribution. We used light-level geolocation to quantify the annual at-sea distribution of tufted puffins between a major Gulf of Alaska nesting colony (Middleton Island) and heretofore unknown migration routes and wintering areas. Geolocator data from 42 complete migration routes of reproductive adult tufted puffins collected primarily between 2018-2020 revealed that both males and females were short-distance migrants, wintering on average 616 km from their breeding colony. Tufted puffins departed the breeding grounds in early September. Males made fewer stops and arrived earlier to wintering areas than females, however the arrival date to the wintering area was later in 2019 compared to 2018. Males took 30.5 ± 16.7 (± standard deviation) days in 2018 and 30.8 ± 24.6 days in 2019 to arrive at wintering areas. Conversely, females took 36.1 ± 16.8 days in 2018 and 59.8 ± 17.3 days in 2019 to arrive at wintering areas. Adult tufted puffins wintered primarily in the deep offshore waters of the eastern Gulf of Alaska and partially in the adjacent Northeast Pacific Ocean over a period of 151.9 days ± 31.6 with spring migrations starting by late March. Males and females showed consistent spatial distributions within seasons, especially during winter. Tufted puffins shifted southwards throughout the non-breeding season, similar to other Atlantic and Northeast Pacific alcids. Our study provides important information on the at-sea non-breeding phenology and distribution of tufted puffins, which can inform risk assessments for the species including vulnerability to spatially and temporally explicit marine pollution, disease, fisheries by-catch, and ocean-climate variability.

Diversity of Viridiplantae DNA present on rock surfaces in the Ellsworth Mountains, continental Antarctica - Paulo E. A. S. Câmara; Graciéle C. A. de Menezes; Fábio S. Oliveira; Caroline Delpupo Souza; Eduardo T. Amorim; Carlos E. G. R. Schaefer; Peter Convey; Otavio H. B. Pinto; Micheline Carvalho-Silva; Luiz H. Rosa (Polar Biology, 2022)

The natural history of OTOF-related auditory neuropathy spectrum disorders: a multicenter study - Ryan K. Thorpe; Hela Azaiez; Peina Wu; Qiuju Wang; Lei Xu; Pu Dai; Tao Yang; G. Bradley Schaefer; B. Robert Peters; Kenny H. Chan; Krista S. Schatz; Joann Bodurtha; et al. (Human Genetics, 2022)

Flow Structure in an Artificial Seagrass Meadow in Combined Wave-Current Conditions - Rachel B. Schaefer; Heidi M. Nepf (Frontiers in Marine Science, 2022)
Experiments were conducted in a laboratory flume using an artificial seagrass meadow, modeled after Zostera marina , to examine the impact of waves on the vertical structure of time-averaged current, Reynolds stress, and turbulent kinetic energy (TKE) under combined wave-current conditions. With the addition of smaller waves, defined by a ratio of wave velocity to current velocity U w /U c < 2.5, the time-averaged velocity peaked above the meadow, which was similar to pure current conditions. When U w /U c > 2.5, the presence of waves caused the time-averaged velocity to peak near the top of the meadow. For U w /U c > 1 the presence of waves reduced the magnitude of peak Reynolds stress. For all conditions considered, the wake production of turbulence dominated the shear production of turbulence in the meadow. However, the wave velocity was less efficient than the current velocity in generating TKE in the meadow because the movement of the blades forced by the oscillatory fluid motion reduced the relative velocity between the blades and the wave. A modified hybrid model for wake production of TKE in a flexible canopy under combined wave-current conditions was proposed to account for the relative contributions of waves and currents. Wake production of TKE was dominated by waves when U w /U c > 1 and dominated by currents when U w /U c < 1. The models and observations proposed in this study contribute to an enhanced understanding of the relative influences of waves and currents on seagrass meadow flow structure in realistic combined wave-current conditions.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Dispersal syndromes are poorly associated with climatic niche differences in the Azorean seed plants - María Leo; Manuel J. Steinbauer; Paulo A.V. Borges; Eduardo B. de Azevedo; Rosalina Gabriel; Hanno Schaefer; Ana M.C. Santos (Journal of Biogeography, 2021)
Aim Environmental niche tracking is linked to the species ability to disperse. While well investigated on large spatial scales, dispersal constraints also influence small‐scale processes and may explain the difference between the potential and the realized niche of species at small scales. Here we test whether niche size and niche fill differ systematically according to dispersal syndrome within isolated oceanic islands. We expect that species with higher dispersal abilities (anemochorous or endozoochorous) will have a higher niche fill, despite their environmental niche size. Location Azores archipelago. Taxon Native seed plants. Methods We combined a georeferenced database of the species distribution within the archipelago (Azorean Biodiversity Portal/GBIF) with an expert‐based dispersal syndrome categorization and a high‐resolution climatic grid (CIELO model). Using four climatic variables (Annual Mean Temperature, Mean Diurnal Range, Annual Precipitation, Precipitation Seasonality), we calculated a four‐dimensional hypervolume to estimate the niche size of each species. Niche fill was quantified as the suitable climatic space of the island that was occupied by the focal species. Results We found a significant relationship between dispersal syndromes and niche size, and also between dispersal syndromes and niche fill. Such relationships presented no phylogenetic signal. Endozoochorous species display higher niche fill compared to epizoochorous and hydrochorous species, and larger niches than anemochorous and epizoochorous. Differences among the remaining groups are not significant for either niche size or for niche fill. Main conclusions The ability of a species to track its niche at small scales is not tightly related to its dispersal syndrome, although endozoochorous species track their niche more efficiently than the rest of groups. Despite being intuitively appealing, dispersal syndrome classifications might not be the most appropriate tools for understanding dispersal processes at small scales.

Water Quality of the Gualaxo do Norte and Carmo Rivers After the Fundão Dam Collapse, Mariana, MG - Felipe C. Santana; Márcio R. Francelino; Carlos E. G. R. Schaefer; Gustavo V. Veloso; Elpídio I. Fernandes-Filho; Adalgisa de J. P. Santana; Lucas B. Timo; André P. Rosa (Water, Air, & Soil Pollution, 2021)

Correction to: Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration - Istem Fer; Anthony K. Gardella; Alexey N. Shiklomanov; Eleanor E. Campbell; Elizabeth M. Cowdery; Martin G. De Kauwe; Ankur Desai; Matthew J. Duveneck; Joshua B. Fisher; Katherine D. Haynes; Forrest M. Hoffman; Miriam R. Johnston; et al. (Global Change Biology, 2021)
In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century.

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

Genomic sequencing of a virus representing a novel type within the species Dyopipapillomavirus 1 in an Indian River Lagoon bottlenose dolphin - Galaxia Cortés-Hinojosa; Kuttichantran Subramaniam; James F. X. Wellehan; Terry Fei Fan Ng; Eric Delwart; Stephen D. McCulloch; Juli D. Goldstein; Adam M. Schaefer; Patricia A. Fair; John S. Reif; Gregory D. Bossart; Thomas B. Waltzek (Archives of Virology, 2019)

PDGF-BB regulates splitting angiogenesis in skeletal muscle by limiting VEGF-induced endothelial proliferation - R. Gianni-Barrera; A. Butschkau; A. Uccelli; A. Certelli; P. Valente; M. Bartolomeo; E. Groppa; M. G. Burger; R. Hlushchuk; M. Heberer; D. J. Schaefer; L. Gürke; et al. (Angiogenesis, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

The growth cessation model: a growth model for species showing a near cessation in growth with application to bigeye tuna (Thunnus obesus) - Mark N. Maunder; Richard B. Deriso; Kurt M. Schaefer; Daniel W. Fuller; Alexandre M. Aires-da-Silva; Carolina V. Minte-Vera; Steven E. Campana (Marine Biology, 2018)

Comparative genetic isolation patterns for multiple headwater fishes in three geographic regions - B. V. Schmidt; J. F. Schaefer (Journal of Fish Biology, 2018)
Headwater‐resident fishes may be prone to a high rate of isolation and a pronounced hierarchical genetic structure due to a combination of niche preference and dendritic effects of river networks. Genetic isolation patterns were compared using microsatellites in six headwater fishes, Fundulus olivaceus , Semotilus atromaculatus , Erimyzon claviformis , Etheostoma artesiae , Etheostoma whipplei and Etheostoma parvipinne , in three geographic regions that included drainages of small, medium and large sizes in the southern United States. All species showed hierarchical nesting of genetic populations and there were clear and mostly consistent differences between species and regions that were identified through summary statistics derived from two independent analyses. For species comparisons, a high isolation grouping (increased number of isolated genetic clusters or sites within regions) and a low‐isolation grouping (decreased number of clusters or sites) were identified. Species group placement was related to niche breadth along the river continuum and presumed abundance and variability of preferred microhabitats, with increased headwater specialization among species being associated with placement in the high‐isolation grouping. There was a weakly significant positive effect of drainage size on the number of isolated clusters or sites across all species. Regional patterns were shared in two species, with the region containing the smallest drainages having lower rates of isolation in both datasets. This study shows the effects of regional and species characteristics on genetic isolation for headwater species, which are especially prone to isolation due to spatial, dendritic effects of river networks.

Potential for cometabolic biodegradation of 1,4-dioxane in aquifers with methane or ethane as primary substrates - Paul B. Hatzinger; Rahul Banerjee; Rachael Rezes; Sheryl H. Streger; Kevin McClay; Charles E. Schaefer (Biodegradation, 2017)

Induction of gonadal maturation at different temperatures in burbot Lota lota - F. J. Schaefer; B. Hermelink; P. Husmann; W. Meeus; J. Adriaen; S. Wuertz (Journal of Fish Biology, 2016)
A rearing experiment was conducted to test whether temperature protocols that differed from a simulation of natural conditions might induce maturation after isothermal grow‐out in burbot Lota lota . Lota lota were acclimated to two different temperature regimes: low temperature ( LT ), close to natural temperature at 4·0° C and elevated, high temperature ( HT ) at 8·5° C over 40 and 27 days respectively, with all fish then wintered for 47 days. Every second fish was treated with a gonadotropin‐releasing hormone analogue. Maturational competence of oocytes was assessed with a germinal vesicle breakdown assay using a novel staining strategy. In both treatments, puberty and maturational progress occurred, characterised by an elevated gonado‐somatic index and advanced gonadal stages (histological analysis). Progress of gonadal maturation was reflected by elevated plasma concentrations of testosterone and 11‐ketosterone in males and 17β‐oestradiol in females. Ovulation was not observed. Sperm could be activated equally across treatments. In general, LT was more effective than HT treatment, indicated by advanced gonadal stages, higher numbers of oocytes undergoing germinal vesicle breakdown in vitro and elevated sex steroid levels. Hormone treatment could improve effectiveness at HT . In conclusion, less drastic temperature regimes as previously reported in combination with hormone treatments seem sufficient to induce maturation in L. lota after isothermal grow‐out.

Pregnancy and Infants’ Outcome: Nutritional and Metabolic Implications - C. Berti; I. Cetin; C. Agostoni; G. Desoye; R. Devlieger; P. M. Emmett; R. Ensenauer; H. Hauner; E. Herrera; I. Hoesli; S. Krauss-Etschmann; S. F. Olsen; et al. (Critical Reviews in Food Science and Nutrition, 2016)

A test of the cosmogenic 3 He production rate in the south‐west Pacific (39°S) - SHAUN R. EAVES; GISELA WINCKLER; JOERG M. SCHAEFER; MARCUS J. VANDERGOES; BRENT V. ALLOWAY; ANDREW N. MACKINTOSH; DOUGAL B. TOWNSEND; MATTHEW T. RYAN; XUN LI (Journal of Quaternary Science, 2015)
Calculation of surface exposure ages, using in situ cosmogenic nuclides, requires accurate knowledge of local production rates. Here, we report the first attempt to calibrate cosmogenic 3 He production in the south‐west Pacific region. We present a new radiocarbon chronology that precisely dates the emplacement of the Murimotu Formation, a large debris avalanche deposit in central North Island, New Zealand (ca. 830 m asl; 39°S), which occurred 10.4–10.6 cal ka BP. Measurements of cosmogenic 3 He in pyroxene separated from large andesitic blocks exposed during this event yield a sea‐level high‐latitude production rate of 120 ± 12 atoms g −1 a −1 (‘Lm’ scaling). This is consistent with a recent global compilation, comprised predominantly of calibration sites located in the Northern Hemisphere. Thus, we conclude that the globally compiled cosmogenic 3 He production rate is valid in the south‐west Pacific. Using independent, proximal calibrations of cosmogenic isotopes 10 Be and 14 C from quartz in New Zealand, we derive cosmogenic 3 He/ 10 Be and 3 He/ 14 C production ratios of 32.2 ± 3.2 and 10.6 ± 1.6, respectively.

Isolation and characterization of microsatellite loci for the blackstripe topminnow Fundulus notatus and their variability in two closely related species - K. A. Feldheim; B. R. Kreiser; B. Schmidt; D. D. Duvernell; J. F. Schaefer (Journal of Fish Biology, 2014)
A total of 17 polymorphic microsatellite loci were isolated from the blackstripe topminnow Fundulus notatus . In a sample of 29 individuals, these loci were found to possess two to 19 alleles with expected heterozygosity values ranging from 0·212 to 0·919 and all but one of the loci conformed to Hardy–Weinberg equilibrium expectations. Many of these loci were polymorphic in the closely related species Fundulus olivaceus and Fundulus euryzonus providing a set of markers that should prove useful in future ecological and evolutionary studies of members of this species complex.

Expert assessment of vulnerability of permafrost carbon to climate change - E. A. G. Schuur; B. W. Abbott; W. B. Bowden; V. Brovkin; P. Camill; J. G. Canadell; J. P. Chanton; F. S. Chapin; T. R. Christensen; P. Ciais; B. T. Crosby; C. I. Czimczik; et al. (Climatic Change, 2013)

Heavy Metals Contamination in Century-Old Manmade Technosols of Hope Bay, Antarctic Peninsula - Marcelo Braga Bueno Guerra; Carlos Ernesto G. R. Schaefer; Paula de Freitas Rosa; Felipe N. B. Simas; Thiago T. C. Pereira; Edenir Rodrigues Pereira-Filho (Water, Air, & Soil Pollution, 2011)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Polymorphism at the avpr1a locus in male prairie voles correlated with genetic but not social monogamy in field populations - N. G. SOLOMON; A. R. RICHMOND; P. A. HARDING; A. FRIES; S. JACQUEMIN; R. L. SCHAEFER; K. E. LUCIA; B. KEANE (Molecular Ecology, 2009)
Integrative studies of genetics, neurobiology and behaviour indicate that polymorphism in specific genes contributes to variation observed in some complex social behaviours. The neuropeptide arginine vasopressin plays an important role in the regulation of a variety of social behaviours, including social attachment of males to females, through its action on the vasopressin 1a receptor (V1aR). In socially monogamous prairie voles ( Microtus ochrogaster ), polymorphism in the length of microsatellite DNA within the regulatory region of the gene ( avpr1a ) encoding the V1aR predicts differences among males in neural expression of V1aRs and partner preference under laboratory conditions. However, understanding the extent to which V1aR mediates variation in prairie vole social and reproductive behaviour observed in nature requires investigating the consequences of avpr1a polymorphism and environmental influences under ecologically relevant conditions. We examined the relationship between avpr1a length polymorphism and monogamy among male prairie voles living in 0.1 ha enclosures during a time similar to their natural lifespan. We found no evidence that avpr1a genotype of males predicts variation in social monogamy measured in the field but some indices of social monogamy were affected by population density. Parentage data indicated that a male’s avpr1a genotype significantly influenced the number of females with which he sired offspring and the total number of offspring sired. Total brain concentrations of V1aR mRNA were not associated with either male behaviour or avpr1a genotype. These data show that melding ecological field studies with neurogenetics can substantially augment our understanding of the effects of genes and environment on social behaviours.

Assessing uncertainty in the integration of aeromagnetic data and structural observations in the Deering Hills region of the Musgrave Province - A. R. A. Aitken; P. G. Betts; B. F. Schaefer; S. E. Rye (Australian Journal of Earth Sciences, 2008)

New insights into the size and timing of the Lawn Hill impact structure: relationship to the Century Zn – Pb deposit - J. A. Salisbury; A. G. Tomkins; B. F. Schaefer (Australian Journal of Earth Sciences, 2008)

Threatened fishes of the world: Alosa alabamae (Jordan and Evermann, 1896) (Clupeidae) - Dwayne W. Meadows; Susan B. Adams; Jacob F. Schaefer (Environmental Biology of Fishes, 2008)

Soil and vegetation carbon stocks in Brazilian Western Amazonia: relationships and ecological implications for natural landscapes - C. E. G. R. Schaefer; E. F. do Amaral; B. A. F. de Mendonça; H. Oliveira; J. L. Lani; L. M. Costa; E. I. Fernandes Filho (Environmental Monitoring and Assessment, 2008)

Phylogenetic relationships among North American Alosa species (Clupeidae) - B. R. Bowen; B. R. Kreiser; P. F. Mickle; J. F. Schaefer; S. B. Adams (Journal of Fish Biology, 2008)
A phylogeny of the six North American species in the genus Alosa , with representatives of three Eurasian species, was generated using mtDNA sequences. This was accomplished by obtaining sequences for three North American species and additional geographical sampling of the other three species. The subgenus Alosa , including the formerly recognized subgenus Caspialosa , formed a strongly supported monophyletic group. Alosa alabamae was part of a polytomy with Alosa sapidissima , which was interpreted to support the recognition of A. alabamae as an incipient, yet distinct, species. The subgenus Pomolobus was not recovered as a monophyletic group. Alosa chrysochloris was basal to all other Alosa , although this position was only weakly supported. Previous work had indicated that Alosa pseudoharengus and Alosa aestivalis are not reciprocally monophyletic, but additional sampling in this study did not detect any further cases of shared haplotypes between the two species. The phylogeny supports previous hypotheses that the evolution of North American Alosa species in the Gulf of Mexico ( A. chrysochloris and A. alabamae ) was the result of two independent events. First, the ancestor of A. chrysochloris was isolated in the Gulf of Mexico, likely by the close of the Suwannee Straits, and this was followed later by dispersal of the ancestor of A. alabamae around the Florida peninsula into the Gulf of Mexico sometime during or after the Pleistocene.

On the relationship between hydrocarbon migration pathways and carbonate mound occurrence in the Porcupine Basin - J. Naeth; R. di Primio; B. Horsfield; R. G. Schaefer; B. M. Krooss (International Journal of Earth Sciences, 2007)

Neural driven angiogenesis by overexpression of nerve growth factor - N. Hansen-Algenstaedt; P. Algenstaedt; C. Schaefer; A. Hamann; L. Wolfram; G. Cingöz; N. Kilic; B. Schwarzloh; M. Schroeder; C. Joscheck; L. Wiesner; W. Rüther; et al. (Histochemistry and Cell Biology, 2006)

Brassinosteroid-stimulated branch elongation in the marubakaido apple rootstock - A. B. Pereira-Netto; C. T. A. Cruz-Silva; S. Schaefer; J. A. Ramírez; L. R. Galagovsky (Trees, 2006)

Nest predation is little affected by parental behaviour and nest site in two African Sylvia warblers - Hans-Christian Schaefer; George W. Eshiamwata; Fred B. Munyekenye; Eva Maria Griebeler; Katrin Böhning-Gaese (Journal of Ornithology, 2005)

Monitoring water content of rat lung tissuein vivo using microwave reflectometry - M. Schaefer; K. Nowak; B. Kherad; W. Gross; S. Post; M. M. Gebhard (Medical & Biological Engineering & Computing, 2004)

Effects of Barriers and Thermal Refugia on Local Movement of the Threatened Leopard Darter, Percina pantherina - Jacob F. Schaefer; Edie Marsh-Matthews; Daniel E. Spooner; Keith B. Gido; William J. Matthews (Environmental Biology of Fishes, 2003)

Fuzzy structure and spatial dynamics of a declining woodland caribou population - James A. Schaefer; Alasdair M. Veitch; Fred H. Harrington; W. Kent Brown; John B. Theberge; Stuart N. Luttich (Oecologia, 2001)

Coding sequence, chromosomal localization, and expression pattern of Nrf1: the mouse homolog of Drosophila erect wing - Laura Schaefer; Heather Engman; Jeffrey B. Miller (Mammalian Genome, 2000)